An intelligent computer-based framework for integrating emotions and aerodynamics in sportsbike design. (7th December 2019) - Farrugia, Philip; Mamo, James; Sant, Tonio
In today's competitive market it is critical to understand how product design connects with the consumer emotionally. Therefore, design engineers must adopt a design for emotion (DFe) approach, whilst applying fundamental principles to enhance the performance of complex artefacts, such as sportsbikes. A sportsbike cannot be designed based on aesthetics only, but rather on a balance between aesthetics and aerodynamic performance, as the design of the outer body itself is what ultimately affects the drag and lift properties. Within this context, a framework for an intelligent computer-based support system was developed, aimed at supporting designers to take emotions and aerodynamics when developing sportsbikes. A proof of concept computerbased tool was implemented and evaluated. Qualitative results gathered from an evaluation conducted with eight practicing product development stakeholders, provide a degree of evidence that the proposed framework is useful in designing sportsbikes with more emotional value and enhanced aerodynamic characteristics.